2009
DOI: 10.1002/arch.20299
|View full text |Cite
|
Sign up to set email alerts
|

Digestive proteolysis organization in two closely related Tenebrionid beetles: red flour beetle (Tribolium castaneum) and confused flour beetle (Tribolium confusum)

Abstract: The spectra of Tribolium castaneum and T. confusum larval digestive peptidases were characterized with respect to the spatial organization of protein digestion in the midgut. The pH of midgut contents in both species increased from 5.6-6.0 in the anterior to 7.0-7.5 in the posterior midgut. However, the pH optimum of the total proteolytic activity of the gut extract from either insect was pH 4.1. Approximately 80% of the total proteolytic activity was in the anterior and 20% in the posterior midgut of either i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 46 publications
2
38
0
Order By: Relevance
“…T. castaneum has a midgut with a pH gradient of an acidic anterior to a neutral to basic posterior. In the acidic anterior midgut, proteolytic activity is mostly by cathepsin L and B cysteine peptidases (Vinokurov et al, 2009;Martynov et al, 2015). Reliance on cysteine peptidase activity in the anterior midgut of tenebrionid larvae is probably an adaptation to degrade inhibitors and protect serine peptidases in the posterior midgut (Prabhakar et al, 2007;Oppert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…T. castaneum has a midgut with a pH gradient of an acidic anterior to a neutral to basic posterior. In the acidic anterior midgut, proteolytic activity is mostly by cathepsin L and B cysteine peptidases (Vinokurov et al, 2009;Martynov et al, 2015). Reliance on cysteine peptidase activity in the anterior midgut of tenebrionid larvae is probably an adaptation to degrade inhibitors and protect serine peptidases in the posterior midgut (Prabhakar et al, 2007;Oppert et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Reliance on cysteine peptidase activity in the anterior midgut of tenebrionid larvae is probably an adaptation to degrade inhibitors and protect serine peptidases in the posterior midgut (Prabhakar et al, 2007;Oppert et al, 2010). Some cysteine peptidases also have become specialized for efficient digestion of cereal proteins (Vinokurov et al, 2009;Goptar et al, 2012;Martynov et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…6, underlined) and three with a minor role when fed a normal diet. In a previous biochemical study, we described seven distinct cysteine peptidase activities from fractionation of gut enzymes in the T. castaneum gut, and all were anionic enzymes mostly in the anterior midgut (Vinokurov et al, 2009); we propose that the seven major cysteine cathepsin digestive genes listed here encode those seven anionic enzymes. Three cathepsin B or B-like genes (LOC657117, LOC657203, and LOC656957) and four cathepsin L genes (LOC659441, LOC659502, LOC660368, and LOC663145) were upregulated when T. castaneum larvae were fed digestive inhibitors ( Fig.…”
Section: Development Of a Functional Model For Cysteine Peptidases Inmentioning
confidence: 67%
“…T. castaneum cysteine peptidase genes include cathepsin B and L peptidases, mostly arranged in clusters on chromosome 3, 7, 8 and 10, and also single genes encoding cathepsins F, K, and O on chromosome 7, 4 and 1(X), respectively. Empirical evidence of the biological function of each cysteine peptidase gene in T. castaneum is lacking, although our previous studies suggest that some function as major processors of food proteins in the larval gut (Oppert et al, 1993;Vinokurov et al, 2009;Oppert et al, 2010;Martynov et al, 2015). Gene expression studies indicated that cathepsin L genes LOC659441 and LOC659502 are the most highly expressed cysteine peptidases in the larval gut and are most likely encoding enzymes important in the early stages of cereal protein digestion, as they are located in the anterior midgut (Prabhakar et al, 2007;Morris et al, 2009;Vinokurov et al, 2009;Martynov et al, 2015).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation